Sistem Pendukung Keputusan Dalam Pemilihan Mahasiswa Terbaik Untuk Program Student Exchange Menggunakan Metode Electre - Sarumaha, Apotes (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The student exchange program carried out by HKBP Nomensen University has had a positive influence and impact in the field of student development and the field of nation building. By conducting student exchanges so that the exchange of knowledge and experience between universities and students is of good quality. In selecting the best students for the student exchange program, several criteria are needed to make a decision. So far, HKBP Nomensen University has selected the best students for the student exchange program manually based on the results of the student achievement index. This system is considered less effective and efficient in selecting the best students for the student exchange program because it takes at least 1 month to make a decision. To support decision making in selecting the best students for the student exchange program, it is easier to use a decision support system. One of the methods used for decision support systems is the Electre (Elimination and Choice Translation Reality) method. The Electre method is a multi-criteria decision making method based on the outranking concept using pairwise comparisons of alternatives based on each appropriate criterion. ELimination Et Chix Traduisant La RealitE (ELECTRE) is a method for determining order (priority) in multicriteria analysis. The decision support system application which is used as a solution to the problem above works based on the ELECTRE method which was built with the Microsoft Visual Studio 2008 programming language which is integrated with the MySQL database to store data which is the criteria, alternatives and rules needed when making decisions by system.